Long-term exposure to a 40-GHz electromagnetic field does not affect genotoxicity or heat shock protein expression in HCE-T or SRA01/04 cells - Koyama, Shin (J Radiat Res, 2019)
Millimeter waves are used in various fields, and the risks of this wavelength range for human health must be carefully evaluated. In this study, we investigated the effects of millimeter waves on genotoxicity and heat shock protein expression in human corneal epithelial (HCE-T) and human lens epithelial (SRA01/04) cells. We exposed the cells to 40-GHz millimeter waves at 1 mW/cm(2) for 24 h. We observed no statistically significant increase in the micronucleus (MN) frequency or the level of DNA strand breaks in cells exposed to 40-GHz millimeter waves relative to sham-exposed and incubator controls. Heat shock protein (Hsp) expression also exhibited no statistically significant response to the 40-GHz exposure. These results indicate that exposure to 40 GHz millimeter waves under these conditions has little or no effect on MN formation, DNA strand breaks, or Hsp expression in HCE-T or SRA01/04 cells.